Students' Perceptions in the Contribution of Project-Based Learning "DIONTANA (Food Chain Diorama)" in Realizing Creative Learning: A Case Study at SD Negeri 5 Metro Selatan - Laila Pratiwi; Nuni Widiarti (Jurnal Inspirasi Pendidikan, 2025)
This study aims to describe elementary school students' perceptions of the contribution of the project-based learning "Food Chain Diorama" in fostering creative learning. Creativity in learning is an essential aspect to develop students' potential holistically. Project-based learning, with its characteristics involving students actively in inquiry processes, collaboration, and the production of tangible works, is believed to stimulate creativity. This research uses a descriptive qualitative approach with a case study design, involving fifth-grade students at SD Negeri 5 Metro Selatan as participants selected through purposive sampling. Data were collected through semi-structured interviews, participatory observation, and documentation during the implementation of the "Food Chain Diorama" project. Data analysis was conducted using the Huberman and Miles model. The results showed that the majority of students had a positive perception of the contribution of the "Food Chain Diorama" project in fostering their creativity. They experienced improvements in their ability to generate new ideas, think flexibly, and imagine while constructing the diorama. Additionally, the collaborative aspect of the project was perceived as contributing to the development of creative ideas through idea exchange among peers. This research implies that project-based learning, especially with engaging and contextual themes such as the food chain, has the potential to be an effective strategy in realizing creative learning at the elementary school level.